Synthesis and translation of research and innovations from polio eradication (STRIPE): Initial findings from a global mixed methods study - Alonge, Olakunle; Neel, Abigail H.; Kalbarczyk, Anna; Peters, Michael A.; Mahendradhata, Yodi; Sarker, Malabika; Owoaje, Eme; Deressa, Wakgari; Kayembe, Patrick; Salehi, Ahmad Shah; Gupta, S. D. (BMC, 2022)
This article was published in BMC Public Health by BMC [ © The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License,] and the definite version is available at: https://doi.org/10.1186/s12889-020-09156-9 The Journal's website is at: https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-020-09156-9